A Survey of Alternative Models of the Aggregate U.S. Labor Market - Kniesner, Thomas J.; Goldsmith, Arthur H. (Journal of Economic Literature, 1987)
We thank Lincoln Anderson, Orley Ashenfelter, Costas Azariadis, David Card, William A. Darity, Jr., Belton Fleisher, Richard Froyen, James J. Heckman, Solomon Polachek, Lawrence H. Summers, and two anonymous referees. Particular thanks go to Didi Dunphy for drafting the figures and to the University of North Carolina, College of Arts and Sciences, Endowment for Scholarly Publications for providingfinancial support. Sarah Mason did her usualfine job of typing, Karen Smith and Jonathan Veum provided valuable computing assistance, and Cynthia McCarty cheerfully checked citations for completeness and correctness. Preliminary versions of this paper have been presented at the 1982 Annual Meetings of the Econometric Society, the Fifth World Congress of the Econometric Society, 1985, and the 1986 Annual Meetings of the Eastern Economic Association.